Promoting gender equality trough equal life standard in EU countries - Aleksandar Dashtevski; Jana Ilieva; Rozalina Popova-Koskarova (UTMS Journal of Economics, 2018)
After the World War II, especially in the early fifties there is an expansion of gender rights. Women are massively employed all over the world in all sectors of social life, contributing to an increase in both their own standard of living and the standard in their own countries. As the importance and role of women grows, this is achieved with increasing respect for its rights. Gender means elimination of inequality and promote equality between women and men in all areas of social life. If we want to achieve gender equality as a whole, it is inevitable to achieve an economic consolidation of the two sexes. Economic strengthening is possible trough equal pay. Experience shows that payments are not equal when it comes to wages for men and women. Therefore, the EU is constantly working to regulate this area, with special regulations, which are mandatory for the member states, but should also be respected by countries that would like to join the union. This led to the promotion of gender equality through an equal life.
Keywords: K38; 330; equality; gender; sex; equal pay; discrimination